PERSONALITY IN TEACHING THE MODULE OF LATIN AND MEDICAL TERMINOLOGY IN THE MEDICAL HIGHER EDUCATION INSTITUTION (Journal of Universal Science Research, 2024)
This article was written on the example of the work carried out at the University on the essence of education aimed at the student’s personality in the teaching of the Latin language and the module of medical terminology in a medical higher education institution.